2021
DOI: 10.1093/pubmed/fdaa257
|View full text |Cite
|
Sign up to set email alerts
|

Technology addiction among school-going adolescents in India: epidemiological analysis from a cluster survey for strengthening adolescent health programs at district level

Abstract: Background There is limited evidence on technology addiction among adolescents in low- and middle-income countries where 90% of global adolescents live. We aimed to investigate the prevalence and correlates of technology addiction (Internet, gaming, smartphone, television) among school-going adolescents in India. Methods A cross-sectional survey covering the entire district (administrative unit for health) of India was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…An Indian study among school-going children, where 57.55% were female, found that 10.69% of technology users were addicted, with 8.91% addicted solely to their phones. 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An Indian study among school-going children, where 57.55% were female, found that 10.69% of technology users were addicted, with 8.91% addicted solely to their phones. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, previous research consisting of two systematic reviews and meta-analysis2 14 confirm the increasing prevalence trend of gadget addiction over time in children and children. An Indian study among school-going children, where 57.55% were female, found that 10.69% of technology users were addicted, with 8.91% addicted solely to their phones 15…”
Section: Discussionmentioning
confidence: 99%
“…The study aimed to identify original research about mental health issues among school children and adolescents aged 19 years and under in India from studies published predominantly between January 2013 and August 2023. To obtain relevant articles, our initial literature search yielded 358 articles, 31 of which were included in this systematic review, the characteristics of which are summarized in The systematic review includes 24 cross-sectional studies [19,20,23,24,[26][27][28][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]46,47], two descriptive cross-section studies [17,18], two comparative cross-section studies [21,29], whereas one randomized control trial [22], one survey study [25], and one intervention study [45] respectively. This review had 30,970 participants, of which 14381 (46.43%) were male.…”
Section: Resultsmentioning
confidence: 99%
“…This review had 30,970 participants, of which 14381 (46.43%) were male. The overall mean age of the school children and adolescents was 14.58 years, with a standard deviation of 1.35 [22,24,[26][27][28][29][35][36][37][38]43,44]. As per participants' concern, the sample size for cross-section studies ranging from 150 to 6682 participants, 242-369 participants for descriptive cross-section studies [17,18] and 462-1000 participants for comparative crosssection studies [21,29], whereas in randomized control trials [22], survey study [25], and intervention study [45], number of participants were 11, 874, and 300 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Nitekim adölesanların %95'inin başta cep telefonu olmak üzere, tablet, diz üstü bilgisayar vb gibi farklı türden sahip oldukları teknolojik araçlarla, günde birkaç kez veya neredeyse sürekli çevrimiçi olarak zaman harcadıkları ifade edilmektedir (16). Bazı adölesanlar teknolojik araçları sadece iletişim aracı olarak kullanırken bazıları film izlemek, müzik dinlemek, çevrimiçi oyun oynamak, alışveriş yapmak, eğitim materyallerine göz atmak gibi değişik amaçlar doğrultusunda kullanmaktadır (2,17). Günümüzde değişik amaçlar doğrultusunda kullanılan teknolojinin aşırı ve gereksiz kullanımı adölesanlarda teknoloji bağımlılığına yol açabilmekte ve bu sorunu önlemede ruh sağlığı alanı başta olmak üzere sağlık profesyonellerine önemli rol ve sorumluluklar düşmektedir (2).…”
Section: Nüksetme (Relapse)unclassified